PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN DENGAN MODERASI LINGKUNGAN KERJA - Serniati Bulu; I Ketut Westra; I Dewa Gede Kresna Wirawan (Arthaniti Studies, 2025)
This study aims to analyze the influence of compensation and work motivation on employee job satisfaction, as well as to evaluate the role of the work environment as a moderating variable at PT. Atika Mandiri. The research was motivated by the initial findings of low job satisfaction levels, indicated by a high turnover rate and negative employee perceptions of compensation, motivation, and the work environment. A quantitative approach was employed with a census method involving all 90 employees as respondents. Data were collected using a questionnaire, and the data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 3.0 software. The results showed that both compensation and work motivation have a positive and significant effect on job satisfaction. Furthermore, the work environment was found to moderate the relationship between compensation and job satisfaction but did not moderate the relationship between work motivation and job satisfaction. These findings suggest that a supportive work environment can strengthen the positive impact of compensation on job satisfaction but does not significantly enhance the effect of motivation. The practical implication highlights the importance of fair compensation policies and a conducive work environment to sustainably improve employee job satisfaction. Keywords: compensation, work motivation, job satisfaction, work environmen t.